Systematic review and meta-analysis of the diagnostic value of four biomarkers in detecting neonatal sepsis in low- and middle-income countries - Chris A Rees; Jamie Lim; Michelle Niescierenko; Julia Rubin-Smith; Alexis Schmid; Adrianna L Westbrook; Rachelle El Helou; Kyra Shreeve; Chloe Rotman; Sindu Govindapillai; Kate Dorney (BMJ Publishing Group, 2023)
Background Biomarkers may enhance diagnostic capability for common paediatric infections, especially in low- and middle-income countries (LMICs) where standard diagnostic modalities are frequently unavailable, but disease burden is high. A comprehensive understanding of the diagnostic capability of commonly available biomarkers for neonatal sepsis in LMICs is lacking. Our objective was to systematically review evidence on biomarkers to understand their diagnostic performance for neonatal sepsis in LMICs.Methods We conducted a systematic review and meta-analysis of studies published in English, Spanish, French, German, Dutch, and Arabic reporting the diagnostic performance of C reactive protein (CRP), erythrocyte sedimentation rate (ESR), white blood cell count (WBC) and procalcitonin (PCT) for neonatal sepsis. We calculated pooled test characteristics and the area under the curve (AUC) for each biomarker compared with the reference standards blood culture or clinical sepsis defined by each article.Results Of 6570 studies related to biomarkers in children, 134 met inclusion criteria and included 23 179 neonates. There were 80 (59.7%) studies conducted in LMICs. CRP of ≥60 mg/L (AUC 0.87, 95% CI 0.76 to 0.91) among 1339 neonates and PCT of ≥0.5 ng/mL (AUC 0.87, 95% CI 0.70 to 0.92) among 617 neonates demonstrated the greatest discriminatory value for the diagnosis of neonatal sepsis using blood culture as the reference standard in LMICs.Conclusions PCT and CRP had good discriminatory value for neonatal sepsis in LMICs. ESR and WBC demonstrated poor discrimination for neonatal sepsis in LMICs. Future studies may incorporate biomarkers into clinical evaluation in LMICs to diagnose neonatal sepsis more accurately.PROSPERO registration number CRD42020188680.